2020
DOI: 10.1063/1.5139534
|View full text |Cite
|
Sign up to set email alerts
|

Jetting from an impacting drop containing a particle

Abstract: We investigate the dynamics of a drop containing a single solid particle impacting on a solid surface. The particle rebounds through the drop during impact and can separate from the deposited liquid above an impact velocity threshold. We show that this threshold can be predicted by a simple energy balance. Moreover, we discover a new type of liquid jetting ejected above the particle faster than the impact velocity. We demonstrate that this jetting is due to the focusing effect of the liquid on the solid substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In Figure a, the restitution coefficients of all complete rebounds that we investigated are plotted as a function of the Weber number and the impact velocity. The scatter of the data shown in the figure is an inevitable phenomenon of experimental investigations of multiphase free-surface flows, including the impact of liquid droplets on solid surfaces, where the underlying hydrodynamics are very complex. , The scatter of the restitution coefficient at low Weber numbers is also enhanced by the existence of inevitable surface defects due to the dominant role of the droplet–surface friction in energy dissipation, though much care has been taken in the surface fabrication. Indeed, existing studies of bouncing droplets on hot surfaces above the Leidenfrost temperature ,, and on sublimation solid surfaces such as dry ice, , where the impinging droplets are always suspended on a thin gas layer without contact with the solid surfaces, reported weakly scattered experimental data of diverse impact characteristics.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In Figure a, the restitution coefficients of all complete rebounds that we investigated are plotted as a function of the Weber number and the impact velocity. The scatter of the data shown in the figure is an inevitable phenomenon of experimental investigations of multiphase free-surface flows, including the impact of liquid droplets on solid surfaces, where the underlying hydrodynamics are very complex. , The scatter of the restitution coefficient at low Weber numbers is also enhanced by the existence of inevitable surface defects due to the dominant role of the droplet–surface friction in energy dissipation, though much care has been taken in the surface fabrication. Indeed, existing studies of bouncing droplets on hot surfaces above the Leidenfrost temperature ,, and on sublimation solid surfaces such as dry ice, , where the impinging droplets are always suspended on a thin gas layer without contact with the solid surfaces, reported weakly scattered experimental data of diverse impact characteristics.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Here, the variables ρ, γ, and η denote the experimental fluids' density, surface tension, and dynamic viscosity, respectively. Most recently, Zhao et al 43 have reported that high-speed liquid jetting during the impact of a droplet containing a spherical particle occurs when the liquid along the solid surface experiences radial-focusing in the air cavity engendered by the rebounding particle previously. On the contrary, the columnar jet is formed on solid surfaces as we increase the impact velocity beyond the singular jet regime.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the automotive industry, particle-fluid interactions and flow of particulate matter in thermal multiphase fluidic environments affect the design of combustion chambers and cyclone separators, as nano-to micron-size particles enhance the heat transfer in fluidic systems [4,5,6]. In industrial processes such as inkjet printing [7,8], additive manufacturing of ceramics and cement [9], and cosmetics [10], the impact of a liquid drop containing solid particles on solid surfaces affects the deposition and splashing dynamics, in which particle-to-droplet size ratio and particle's wettability play critical roles [11]. In biomedical fields, the geometric shape, size, deformability, concentration, and surface properties are critical design parameters for engineered particles [12] used for optimal deliveries of nanomedicine and chemotherapeutics to targeted tumor cells for enhanced treatments [13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%